USE OF SOCIAL MEDIA IN POLITICAL COMMUNICATION - Muhammad Budiana (Jurnal Info Sains : Informatika dan Sains, 2022)
The rising sophistication of information and communication technologies poses a communication problem for political parties and political actors. Social media provides not just rapid information but also exact categorization. In politics, communication strategy is one of the keys to success in garnering votes. This study tries to determine the social media-based political communication approach. This is a qualitative study employing a descriptive analysis methodology. Interview- and literature-based data collection. The results indicate that the use of social media is not constrained by social, economic, or political status; social media and mainstream mass media have different characteristics when it comes to disseminating messages to audiences; and social media is a supporter of political communication in democratic countries where developing traditional and social media for political communication may be the best way to maintain audience engagement and communication